Phytochemical Content of Fresh Purple Sweet Potato (Ipomea batatas L.) Extract As Acid-Base Titration Indicator - Anjelina Derci Jenimat; Yustina D Lawung; Anselmus Boy Baunsele; Erly Grizca Boelan; Theresia Wariani; Maria Aloisia Uron Leba (Universitas Nusa Bangsa, 2023)
Research has been carried out to examine the extraction and application of purple sweet potato tuber extract as an indicator of acid-base titration. Purple sweet potato tuber extract was obtained by extracting fresh tubers using ethanol 95% medical grade (PSPTE-95%) and ethanol 96% analytical grade (PSPTE-96%). Three variations of the maceration stage extracted samples. The extract was used for a phytochemical test and applied as an indicator for acid-base titration. Based on the research conducted, the rendement extract was extracted by ethanol 95% medical grade (PSPTE-95%) for the three stages of maceration are 4.34%, 4.76%, and 5.64%, the rendement extract was extracted by ethanol 96% analysis grade (PSPTE-96%) for the three stages of maceration are 7.09%, 12.16%, and 20.43%. PSPTE-95% and PSPTE-96% contain flavonoids, tannins, alkaloids, and saponins. PSPTE-95% and PSPTE-96% can be applied as indicators for titration of HCl solution with NaOH solution and HCl solution with NH4OH solution.